Paper like free-standing hybrid single-walled carbon nanotubes air electrodes for zinc–air batteries - Gupta, Nutan (2013)
Flexible electrode architectures based on non-functionalized (P2) and functionalized (P3) single-walled carbon nanotubes (SWNTs) were fabricated via a simple vacuum filtration process. A hybrid layer of various compositions of P2- and P3-SWNTs forms free-standing membranes (~80 μm in thickness), and their electrochemical performance was evaluated as an air electrode AEP2/P3 in zinc–air batteries. Such bifunctionalized air electrodes showed uniform surface morphology with interconnected micron-sized porous structure with high porosity (~70%). The N2 adsorption isotherms at 77 K are of type IV with BET-specific surface areas of AE(60/40) and AE(80/20) to be 130.54 and 158.76 m^(2) g^(−1), respectively, thus facilitates high active surface area for active oxygen reduction/evolution reactions. BJH pore size distribution of AE(60/40) and AE(80/20) shows maximum pores with diameter <15 nm. The zigzag interlaying of the SWNTs imparts mechanical stability and flexibility in zinc–air batteries. Zinc–air batteries with optimized compositions of P2- and P3-SWNTs in air electrode AE(60/40) had ionic conductivity ~1 × 10−2 S cm^(−1) and delivered higher discharge capacity ~300 mAh g^(−1) as compared to AE(80/20) composition. The unique properties of AE(P2/P3) studied in this work would enable flexible air electrode architectures in future metal–air batteries.